TREATMENT OF MALOCCLUSION WITH SEVERE CROWDING AND MESIODENS TEETH USING THE PIGGYBACK TECHNIQUE ON STRAIGHT WIRE (CASE REPORT) - Winarno, Bawa Adi (Indonesian Journal of Dentistry, 2024)
Background: One malocclusion condition is accompanied by crowding due to a discrepancy between arch and tooth size. Piggyback technique in orthodontics to correct malpositioned teeth without disturbing the stability of the main arch. The aim of this case report is to guide clinicians in using the piggyback technique as a technique that can be used in treating cases of class I malocclusion accompanied by severe crowding without disturbing the stability of the main arch. A 22 year old female patient with the main complaint of severe crowding of the anterior teeth. The analysis and diagnosis results showed Angle class I malocclusion accompanied by maxillary anterior crowding, rotation of teeth 11, 12, 13, palatal ectopic of tooth 25, buccal ectopic of tooth 33, and anterior-posterior mandibular crowding. There was a median line shift of 2 mm to the left, skeletal relationship class 1. Panoramic showed the presence of supernumerary teeth between 11 and 21, superficial caries on tooth 11, and caries reaching the pulp on tooth 26. All permanent teeth had erupted, and impaction on tooth 48. The piggyback technique used is by modifying two wires plus the use of an open NiTi coil spring, where some of the 0.012 NiTi flexible wire segments on the jaw arch are joined with SS 0.017 x 0.025 stiff wire throughout the segments. Treatment results showed corrected maxillary and mandibular crowding, rotation of teeth 11, 12, 13, palatal ectopic of tooth 25, buccal ectopic of tooth 33, overjet, corrected deep bite, and corrected mandibular median line shift. The profile improves, the patient's smile becomes more attractive with the teeth at good level and alignment and the facial profile becomes straighter.